Application of Carbon Materials in Aqueous Zinc Ion Energy Storage Devices. Issue 19 (19th March 2021) - Wang, Ziting; Zhang, Maoqin; Ma, Weiting; Zhu, Junbo; Song, Weixing
Abstract: Zinc‐ion storage is a promising electrochemical energy field due to loads of its advantages like easy preparation, environmental friendliness, high safety performance, and high capacity. Carbon materials have been widely studied for zinc‐ion storage due to their extraordinary properties such as earth‐abundancy, low‐cost, good electrical conductivity, various structures, and good stability. This article reviews some widely used carbon materials in zinc ion storage devices, including hollow carbon spheres, activated carbon, N‐doped porous carbon, graphene, and carbon nanotubes. The unique roles and advantages of these carbon materials in both zinc ion supercapacitors and zinc ion batteries are emphasized. Characteristics and functionalizations of different carbon materials are also comparatively discussed in view of zinc‐ion energy storage devices. Finally, some challenges and perspectives of carbon materials in zinc‐ion energy storage are outlined. Abstract : The applications of carbon‐based electrode materials including hollow carbon spheres, activated carbon, N‐doped porous carbon, graphene, and carbon nanotubes in aqueous zinc‐ion energy storage devices are reviewed. These materials with large specific surface area and good electrical conductivity can be integrated in cathodes of ZIBs to improve the energy storage and output performance.